2011
DOI: 10.1002/adfm.201100886
|View full text |Cite
|
Sign up to set email alerts
|

ph‐Dependent Synthesis of Pepsin‐Mediated Gold Nanoclusters with Blue Green and Red Fluorescent Emission

Abstract: This report demonstrates the fi rst pH-dependent synthesis of pepsinmediated gold nanoclusters (AuNCs) with blue-, green-, and red-fl uorescent emission from Au 5 (Au 8 ), Au 13 , and Au 25 , respectively. Pepsin is a gastric aspartic proteinase (molecular weight, 34 550 g/mol) that plays an integral role in the digestive process of vertebrates. It was found that the pH of the reaction solution was critical in determining the size of Au NCs (i.e., the number of gold atoms of AuNCs). Interestingly, enzyme funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
370
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(401 citation statements)
references
References 35 publications
15
370
0
3
Order By: Relevance
“…These are bovine serum albumin (BSA), trypsin, pepsin, horseradish peroxidase, lactoferrin, human serum transferrin, lysozyme, and cellular retinoic acid-binding protein 2 (CRABP2) [14][15][16][17][18][19][20][21]. Proteinconjugated gold clusters are already applied as analytical sensors of Hg 2+ , Pb 2+ moreover, BSA-protected clusters do not show significant toxicity in vitro [25], which allows their application in biological systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are bovine serum albumin (BSA), trypsin, pepsin, horseradish peroxidase, lactoferrin, human serum transferrin, lysozyme, and cellular retinoic acid-binding protein 2 (CRABP2) [14][15][16][17][18][19][20][21]. Proteinconjugated gold clusters are already applied as analytical sensors of Hg 2+ , Pb 2+ moreover, BSA-protected clusters do not show significant toxicity in vitro [25], which allows their application in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, investigation on the oxidation state of gold suggested that Au I and Au 0 could be both present in the clusters [14][15][16]18], which implicates that different residues are involved in the process. It has been demonstrated that cysteine is not the only amino acid by which Au I species can be formed: methionine can also reduce gold salts in a similar manner [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of AuNCs at various pH in the presence of pepsin was recently reported, where a broad range of emission colors were obtained. 19 The AuNCs prepared with A30 has a slightly longer emission peak centered at ~480 nm ( Figure 3E). The 5 excitation spectrum shows a peak at 280 nm, which is 20 nm longer than the absorption peak of poly-A DNA.…”
mentioning
confidence: 98%
“…Tseng's group presented a novel approach for preparing highly fluorescent Au 8 NCs and Au 25 NCs by using lysozyme type VI (Lys VI) at pH 3 and pH 12, [43] respectively [49]. Inspired by this finding, researchers try to explore other proteins as efficient bioscaffolds for synthesizing AuNCs such as insulin [50], transferrin-family proteins [51,52], horseradish peroxidase [53], pepsin [54], denatured BSA [55], ribonuclease A [56], trypsin [57], DNase I [58], ovalbumin [59], and egg white [60].…”
Section: Proteinsmentioning
confidence: 99%